Preliminary Study to Test the Feasibility of Sex Identification of Human (Homo sapiens) Bones Based on Differences in Elemental Profiles Determined by Handheld X-ray Fluorescence - Nganvongpanit K. (2017)
© 2016, Springer Science+Business Media New York. Sex assignment of human remains is a crucial step in forensic anthropological studies. The aim of this study was to examine elemental differences between male and female bones using X-ray fluorescence (XRF) and determine if elemental profiling could be used for sex discrimination. Cranium, humerus, and os coxae of 60 skeletons (30 male, 30 female) from the Chiang Mai University Skeletal Collection were scanned by XRF and differences in elemental profiles between male and female bones determined using discriminant analysis. In the cranium, three elements (S, Ca, Pb) were significantly higher in males and five elements (Si, Mn, Fe, Zn, Ag) plus light elements (atomic number lower than 12) were higher in females. In humerus and os coxae, nine elements were significantly higher in male and one element was higher in female samples. The accuracy rate for sex estimation was 60, 63, and 61 % for cranium, humerus, and os coxae, respectively, and 67 % when data for all three bones were combined. We conclude that there are sex differences in bone elemental profiles; however, the accuracy of XRF analyses for discriminating between male and female samples was low compared to standard morphometric and molecular methods. XRF could be used on small samples that cannot be sexed by traditional morphological methods, but more work is needed to increase the power of this technique for gender assignment.